2021
DOI: 10.3390/ijerph182312363
|View full text |Cite
|
Sign up to set email alerts
|

Increased Work from Home and Low Back Pain among Japanese Desk Workers during the Coronavirus Disease 2019 Pandemic: A Cross-Sectional Study

Abstract: To prevent the spread of coronavirus disease 2019 (COVID-19), desk workers in Japan have been encouraged to work from home. Due to rapidly increased working from home, working in environments that are not properly designed and working with poor posture can affect low back pain (LBP). This study aimed to examine the relationship between increased work from home during the COVID-19 pandemic and LBP among Japanese desk workers. Using study data from the Japan COVID-19 and Society Internet Survey 2020 conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
0
17
1
2
Order By: Relevance
“…Correspondingly, three earlier studies reported an association between working from home and pain in these body parts (13,14,17). However, earlier studies also observed an association with pain in the lower back (13,(15)(16)(17), while this was unexpectedly not found in the current study. Still, in the studies that included multiple body regions, larger effect estimates were generally observed for pain in the upper back and pain in the arm, neck, and/or shoulder than for pain in the lower back (13,14,17).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Correspondingly, three earlier studies reported an association between working from home and pain in these body parts (13,14,17). However, earlier studies also observed an association with pain in the lower back (13,(15)(16)(17), while this was unexpectedly not found in the current study. Still, in the studies that included multiple body regions, larger effect estimates were generally observed for pain in the upper back and pain in the arm, neck, and/or shoulder than for pain in the lower back (13,14,17).…”
Section: Discussioncontrasting
confidence: 67%
“…Even before the COVID-19 pandemic, the physical health of workers has been suggested to be negatively impacted by working from home (12). During the COVID-19 pandemic, some studies (13)(14)(15)(16)(17), but not all (18, 19), found a positive association between working from home and musculoskeletal pain. We previously found Dutch home workers to be more likely to report musculoskeletal pain than location workers during the first year of the COVID-19 pandemic (20).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study conducted among computer users working from home during the COVID-19 pandemic, most participants sat on a chair or bed without a desk and worked for long hours while in faulty posture. As a result, 42.9% of them had pain in the neck, and upper back, with up to 41.9%, 24.8%, and 3.1% had mild, moderate, and severe functional limitations due to neck pain [ 14 ]. A recent study conducted in Turkey and published in 2021 indicated that the upper back and neck have a higher prevalence of musculoskeletal pain among smartphone users, particularly with smartphone addiction [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dengan adanya pandemi tersebut turut mengubah gaya hidup masyarakat, yang semula banyak beraktifitas di luar ruangan, menjadi lebih banyak beraktifitas di dalam ruangan/ dirumah yang dikenal dengan istilah bekerja dari rumah/Work From Home (WFH). Sudah banyak yang merasakan dampak dari pandemi Covid-19 mulai dari karyawan maupun perusahaan akibat dari pola work from home, antara lain stress hingga penurunan kinerja hingga (Minoura, 2021;Suresh, 2020, Megsari, 2021 Hal ini tentu berdampak pada perusahaan baik berskala besar maupun kecil yaitu Usaha Mikro Kecil dan Menengah. Penyebaran virus Corona juga berdampak pada sektor investasi,perdagangan,,usaha mikro, kecil dan menengah (UMKM).…”
Section: A Pendahuluanunclassified